Targeting CD47 as a cancer therapeutic strategy: the cutaneous T-cell lymphoma experience. Issue 5 (September 2018) - Folkes, Alecia S.; Feng, Mingye; Zain, Jasmine M.; Abdulla, Farah; Rosen, Steven T.; Querfeld, Christiane
Abstract : Purpose of review: To describe the relevance of CD47 in the tumor microenvironment and summarize data on anti-CD47 therapies, including its role in cutaneous T-cell lymphoma (CTCL). Recent findings: CD47 is expressed on all normal cells and targets SIRPα on the surface of myeloid cells. However, CD47 is found to be overexpressed on cancer cells. CD47–SIRPα interaction inhibits macrophage phagocytosis, allowing cancer cells to escape immune surveillance. Current focus in immunotherapy has been targeted toward inhibiting CD47–SIRPα interaction via anti-CD47 antibodies. This activates innate immunity, promoting cancer cell destruction by macrophages. It also activates adaptive immunity resulting in antigen-presentation, mostly by dendritic cells, leading to antitumor cytotoxic reactions. Current CD47 antagonists undergoing clinical trials include Hu5F9 (an anti-CD47 antibody that directly inhibits the CD47–SIRPα interaction) and TTI-621, (a fusion protein composed of CD47 binding domain of human SIRPα and linked to the Fc region of IgG1). These agents have continued to show strong efficacy against solid and hematological tumors. Summary: In the CTCL tumor microenvironment, increased immune checkpoint inhibition expression via CD47 bound to SIRPα correlates with a more advanced disease state. Continued success in treating these patients requires further studies on CD47 antagonists, specifically when combined with other antibodies.